Mathematical Discourse : Language, Symbolism and Visual Images. - O'Halloran, Kay (Bloomsbury Publishing, 2008)
This book examines mathematical discourse from the perspective of Michael Halliday''s social semiotic theory. In this approach, mathematics is conceptualized as a multisemiotic discourse involving language, visual images and symbolism. The book discusses the evolution of the semiotics of mathematical discourse, and then, proceeds to examine the grammar of mathematical symbolism, the grammar of mathematical visual images, intersemiosis between language, visual images and symbolism and the subsequent ways in which mathematics orders reality. The focus of this investigation is written mathema.